In Search of Treasure in Šalek: Creating Local Identity through Narrative Ostension - Kvartič, Ambrož (Studia mythologica Slavica, 2024)
People transform concrete real-life events into narratives, but the reverse is also true; folklore and narratives in general can also provoke a creative or active response in people and significantly shape their worldview and way of life. The cases in which this happens (through processes of narrative ostension) are also of interest to folklorists, as they provide crucial contextual information about how (folk) narratives function, spread and acquire meaning. Stories about hidden or buried treasure are among the most important narratives that provoke such ostensive (re)actions. People who live with them sometimes venture out into the symbolically significant but very real elements of local space (e.g. castles) and actively search for the treasure mentioned in a legend. Such is the case of Šalek Castle (in Velenje), where local folklore about buried treasure has prompted several generations of locals to head up to the castle and start digging.